A new catfish of the genus Glyptothorax from the Kaladan basin, Northeast India (Teleostei: Sisoridae) - Rameshori, Yumnam; Vishwanath, Waikhom (Zootaxa, 2012)
Glyptothorax churamanii, a new sisorid catfish species from the Kaladan basin of Mizoram State, Northeast India isdescribed. It is distinguished from the congeners of Glyptothorax in the NE Indian region by the combination of thefollowing characters: an oblong thoracic adhesive apparatus opening caudally with an inverted V-shaped mediandepression on its posterior half; the ventral lobe of the caudal fin longer than the dorsal lobe, with diffused blacksubmarginal bands on each lobe; sparsely tuberculate skin; ventral surfaces of pectoral spine and first (and sometimessecond) rays of pelvic fins pleated, plicae on pectoral spine arranged in rows, continuous distally and dissociated in a series of three to five hexagonal-shaped spots in each row; and 3+10 rakers on the first branchial arch.